Simulation of prehepatic portal hypertension and impact of hepatic deportalization on its tissue - О. S. Godik (Клінічна хірургія)
Objective. On the prehepatic portal hypertension pattern, created by partial ligature of venae portae in rats, to estimate the impact of partial hepatic deportalization on its tissue.